Application of DNA and immunoassay analytical methods for GMO testing in agricultural crops and plant-derived products - Kesar Singh, Jasbeer Kaur; Mohamad Ghazali, Farinazleen; Cheah, Yoke Kqueen; Radu, Son (Universiti Putra Malaysia Press, 2008)
The introduction of new agricultural commodities and products derived from modern biotechnology may have an impact on human and animal health, the environment and economies of countries. As more Genetically Modified Organisms (GMO) enter markets worldwide, the monitoring of GMOs is being preferred for obvious reasons such as determination of seed purity, verification of non-GMO status of agricultural crops and fulfilling GMO labeling provisions, to mention a few. Numerous GMO analytical methods which include screening, identification and quantification have been developed to reliably determine the presence and/or amount of GMO in agricultural commodities, in raw agricultural materials and in processed and refined ingredients. The detection of GMOs relies on the detection of transgenic DNA or protein material. For routine analysis, a good sample preparation technique should reproducibly generate DNA/protein of sufficient quality, purity and yield while minimizing the effects of inhibition and contamination. The key sample preparation steps include homogenization, pretreatment, extraction and purification. Due to the fact that analytical laboratories receive samples that are often processed and refined, the quality and quantity of transgenic target analyte (e.g. protein and DNA) frequently challenge the sensitivity of any detection method. With the development of GMO analysis techniques, the Polymerase Chain Reaction (PCR) technique has been the mainstay for GMO detection, and the real-time PCR is the most effective and important method for GMO quantification. The choice of target sequence; for example a promoter, a terminator, a gene, or a junction between two of these elements, is the single most important factor controlling the specificity of the PCR method. Recent developments include event-specific methods, particularly useful for identification and quantification of GM content. Although PCR technology has obvious limitations, the potentially high degree of sensitivity and specificity explains why PCR in its various formats, is currently the leading analytical technology employed in GMO analysis. Comparatively, immunoassays are becoming attractive tools for rapid field monitoring for the integrity of agricultural commodities in identity preservation systems, whereby non-specialised personnel can employ them in cost-effective manner. This review discusses various popular extraction methodologies and summarises the current status of the most widely used and easily applicable GMO analysis technologies in laboratories, namely the PCR and immunoassay technologies.